ENHANCING OR INHIBITING? THE DUAL ROLE OF AL TOOLS IN EFL WRITING PRACTICES - Firda Ziyana Untsa; Ulin Nuha (Esteem Journal of English Education Study Programme, 2025)
This study investigates the dual role of Artificial Intelligence (AI) tools in supporting English as a Foreign Language (EFL) writing. Tools like Grammarly and ChatGPT are found to enhance students’ technical writing accuracy such as grammar, vocabulary, and sentence structure by offering instant feedback. However, concerns persist regarding their limited contribution to the development of higher-order writing skills. Conducted with 100 Indonesian tertiary-level EFL students, this mixed-methods research used surveys and interviews to evaluate the impact of AI tools on writing performance. Quantitative results showed a moderate positive correlation (Spearman’s ρ = 0.450, p = 0.001) between frequent AI use and improvements in surface-level writing. However, participants scored low on creativity and originality (M = 2.37), implying that AI-assisted writing tends to be rigid and lacks personal voice. Qualitative data also highlighted that AI-generated feedback lacks the depth and contextual sensitivity of human instruction. The study concludes that while AI tools are useful for supporting basic writing accuracy, they should not replace teacher feedback. Instead, a blended approach combining AI tools with human guidance is recommended to foster critical thinking, creativity, and rhetorical skills, ensuring more comprehensive EFL writing development.